PENGARUH PEMBERIAN EKSTRAK DAUN PEGAGAN (Centella asiatica) PADA KETAHANAN MUKOSA LAMBUNG (GASTROPROTEKTIF) TIKUS YANG MENGALAMI STRES IMMOBILISASI - Okatiranti Okatiranti (Majalah Obat Tradisional, 2011)
One of the traditional medicinal plants are believed to be as anti-ulcer effect is pegagan (Centella asiatica), pegagan extract thought can protect the gastric mucosa exposed to ethanol by increasing the integrity of the mucosal line of defense. This study aimed to determine the effect of Centella asiatica on rats gastric mucosal resistance (gastroprotective) which experience stress immobilizing. This research is experimental in vivo studies, conducted with 5 groups of male wistar rats treated with 6 replications. Group I is the normal diet control group; group II, normal diet control group mixed Centella asiatica 1 g / mm day; group III was a control group of mice that immobilization stress without giving prior pegagan, Group IV and V is the group that previously received pegagan diet for 3 days prior to immobilization stress with gotu kola concentration of 0.5 g / day and 1.0 g mm / dd day. After 2 days of treatment immobilization stress were measured both in the macroscopic parameters of extensive ulceration and bleeding and microscopic scores for parameters of edema, leukocyte infiltration, and necrosis of rat gastric tissue. The results of macroscopic observations showed that the area of ulceration and bleeding scoring groups I, II, III, there are differences in microscopic bemakna and proven for the parameters of edema, leukocyte infiltration and necrosis are also significant differences. As for group III, IV and V at all test parameters no significant difference.